99mTc-labeled porphyrin–lipid nanovesicles. (June 2015) - Lee, Jae-Ho; Shao, Shuai; Cheng, Kenneth T.; Lovell, Jonathan F.; Paik, Chang H.
Abstract Porphyrin–lipid nanovesicles (PLN) have been developed with intrinsic capabilities as activatable multimodal photonic contrast agents. Radiolabeling of PLN encapsulating drugs could eventually be able to provide quantitative in vivo information for diagnosing and treating diseases. In this study, we developed 99mTc-labeled porphyrin–lipid nanovesicles (99mTc-PLN) as a cargo-encapsulated formulation without significant impact on liposome integrity and encapsulation stability. 50 mM calcein was encapsulated into PLN by probe sonication. The size of the PLN was about 150 nm. The PLN were then reacted with 99mTc using SnCl2 dissolved in 1 mM HCl as a reducing agent and incubated for 10 min at 22 °C. The radiolabeling efficiency and stability of 99mTc-PLN were evaluated by instant thin-layer chromatography and low-pressure liquid chromatography (LPLC). 99mTc labeling was successful with a >92% labeling efficiency. LPLC showed that the liposomal elution peaks of the porphyrin–lipid and the calcein overlapped with the radioactivity elution peak of 99mTc-labeled PLN. The 99mTc-labeling procedure did not change the size of PLN. Encapsulated calcein remained inert inside PLN. Thus, this work lays out a simple and effective radiolabeling method using SnCl2 in HCl in the preparation of 99mTc-PLN.